An organic record of terrestrial ecosystem collapse and recovery at the Triassic–Jurassic boundary in East Greenland - Williford, Kenneth; Grice, Kliti; Holman, Alex; McElwain, J. (Pergamon, 2014)
Terrestrial ecosystem collapse at the end of the Triassic Period coincided with a major mass extinction in the marine realm and has been linked to increasing atmospheric carbon dioxide, global warming, and fire activity. Extractable hydrocarbons in samples from the fluvial Triassic–Jurassic boundary section at Astartekløft, East Greenland were analyzed to investigate the molecular and isotopic organic record of biotic and environmental change during this event. Carbon isotopic compositions of individual plant wax lipids show a >4‰ negative excursion coinciding with peak extinction and a further decrease of 2‰ coinciding with peak pCO2 as estimated from the stomatal indices of fossil Gingkoales. An increase of ∼30‰ in the hydrogen isotopic compositions of the same plant wax lipids coincides with ecosystem collapse, suggesting that the biotic crisis was accompanied by strong hydrologic change. Concentrations of polycyclic aromatic hydrocarbons related to combustion also increase together with abrupt plant diversity loss and peak with fossil charcoal abundance and maximum plant turnover, supporting the role of fire in terrestrial extinctions. Anomalously high concentrations of a monoaromatic diterpenoid related to gymnosperm resin derivatives (and similar to dehydroabietane) occur uniquely in samples from the boundary bed, indicating that environmental stress factors leading to peak plant extinction stimulated increased resin production, and that plant resin derivatives may be effective biomarkers of terrestrial ecosystem stress.